Analysis of drug residue in needle-exchange syringes in Washington, D.C. (December 2021) - Evans, Alexandra; Krause, Michael; Leach, Samantha; Levitas, Morgan; Nguyen, Lucy; Short, Luke C.
Highlights: First analysis of drug residue in needle-exchange syringes collected in Washington, D.C. Developed method to monitor intravenous geospatial drug trends and surveil for novel emerging synthetic substances. 1187 syringes analyzed, over a nine-month period, using gas chromatography mass spectrometry (GC-MS). Fentanyl was the number one detected substance, followed by heroin, cocaine, and methamphetamine, respectively. Abstract: For the first time in Washington, D.C., an analysis of drug residue from used needle-exchange syringes has been performed. This analysis is part of a larger initiative to understand the District of Columbia's illicit drug supply and its intravenous (IV) user's consumption trends as our nation faces the opioid epidemic. The goal of this study is to develop a more comprehensive monitoring program that provides real-time analysis necessary for public health organizations, in addition to providing initial observations of drugs detected. A total of 1187 syringes were analyzed over a period of nine months. Of these, 732 syringes (61.7%) were confirmed to contain a controlled dangerous substance (CDS). Fentanyl was detected in 490 syringes, the most observed CDS in all syringes analyzed. Heroin was the second most detected CDS, observed in 192 syringes. The third most detected CDS was cocaine, which was observed in 132 syringes, followed by the fourth most detected CDS, methamphetamine, observed in 82 syringes. Novel findings of this study include the first reported detections of methamphetamine, synthetic cathinones, and synthetic cannabinoids in used syringes in D.C. Ninety-seven syringes that contained no CDS contained a non-controlled substance of interest, such as diphenhydramine, xylazine, and etizolam. One limitation of this study is that this method cannot determine whether mixtures present in syringes stem from mixtures present prior to injection, back-to-back usage, or sharing of needles. This preliminary study illustrates the strength of surveillance to monitor drug trends and can be used to detect emerging novel dangerous substances in the future.